Efficacy of 0.25% Bupivacaine Alone vs. with Dexmedetomidine for Ultrasound-Guided Supraclavicular Block in Upper Limb Surgery: 0.25% Bupivacaine with Dexmedetomidine for Ultrasound-Guided Supraclavicular Block - Sabir, Sara; Niazi, Rehan Hassan Khan; Imran, Shahzad; Asghar, Hafiz Faheem; Ashfaq, Shumaila; Muzaffar, Aamna (Pakistan Journal of Health Sciences, 2025)
The pain after upper limb surgeries can be intense. The brachial plexus block is an effective and commonly used method to manage this pain, reduce opioid use, and facilitate smoother recovery. Objective: To see the effect of combining bupivacaine with dexmedetomidine in upper limb surgeries. Methods: Quasi-experimental research was carried out at Islam Medical College, Sialkot. 100 patients undergoing upper limb surgeries who were aged between 25 to 65 years. All the patients who were comprised allergies to study drugs, severe organ impairment, coagulopathy, neurological disorders affecting pain perception, and pregnancy were excluded and divided to receive either 0.25% bupivacaine alone or with dexmedetomidine. The outcome variables included pain, analgesia duration, sensory/motor block onset, and 24-hour analgesic consumption. Data were analyzed by SPSS version 23.0. The comparison of quantitative data was done by an independent sample t-test and chi-square test for insightful comparisons between qualitative variables, with the significance level at p-value<0.05. Results: The average age of patients was 40.1 ± 11.5 and 39.8 ± 10.5 years in Group I and Group II, respectively. Male were more in both groups. Group II showed significantly longer analgesia duration (12.7 vs. 5.3 hours), faster sensory/motor block onset, and lower analgesic consumption (p<0.001). There were no significant differences in adverse effects. Conclusions: It was concluded that combining dexmedetomidine with bupivacaine significantly extended analgesia, quickened sensory and motor block onset with a reduction in overall consumption of analgesia. Although sedation was more frequent, no major adverse events were observed.